Equality and the elderly. Between utopias and realities - Verdecia Rodríguez, Asseneth (Espergesia, 2020)
Population aging is a new phenomenon in society at the end of the 20th century with a notable upward trend, which will pose different challenges in all areas of human life. The older adult population therefore requires special protection, supported by legal norms tempered with the contemporary socioeconomic context and by adequate and harmonious public social policies. This makes it essential not only the recognition of their rights inherent to their condition as a human being with different physiological characteristics and in a state of vulnerability, but also a view from Equality as a right and basic and fundamental principle, above all, because its practice allows enjoyment of other rights. The correct and conscious interpretation of the Equality will contribute to guaranteeing the comprehensive care, treatment and protection demanded by older adults, so that the full exercise of their rights passes from utopia to a concrete and possible reality.